Mosaicplasty with photooxidized, mushroom shaped, bovine, osteochondral xenografts in experimental sheep - von Rechenberg, B.; Akens, M. K.; Nadler, D.; Bittmann, P.; Zlinszky, K.; Kästner, S. B. R.; Auer, J. A. (Veterinary and Comparative Orthopaedics and Traumatology, 2006)
The goal was to study the performance of mushroom shaped, photooxidized, osteochondral grafts in mosaicplasty focusing on graft stability and survival. Mushroom shaped, photooxidized grafts (6 mm for the cartilaginous head of the mushroom, 3 mm for the stem) were implanted in the medial femoral condyle of 10 sheep. Four transplants were inserted per condyle in an overlapping fashion using the pressfit technique (n=40 grafts in 10 condyles). The grafts were followed for 6 and 12 months. Semi-quantitative evaluation of graft performance was performed using a validated score system. All grafts were mechanically stable at 6 and 12 months with one exception, where the mushroom head broke off. The formation of cystic lesions in the subchondral bone area was minimal. Repopulation of the old photooxidized cartilage was noticed with cells invading the matrix from the subchondral bone area and also from the pannus on the surface. Fusion between host and graft cartilage was observed in some of the grafts at 12 months, while remodeling of the calcified cartilage zone and tidemark was noticed in all grafts. Results scored significantly better for the 6 months compared to the 12 months group if cartilage surface integrity was compared (p<0.05). In all other variables no significant differences were found between groups. Despite moderate graft recession in the 12 months group partial fusion of grafts and functional results were satisfactory. The photooxidized mushroom shaped osteochondral transplants may be a suitable type of graft for functional results in cartilage resurfacing if stable anchorage of the grafts can be achieved.
Keywords: Osteochondral grafts; photooxidation; mosaicplasty